Revision of the Ambrysus hybridus Montandon species complex (Heteroptera: Naucoridae: Cryphocricinae) with the description of a new species from Mexico - Reynoso-Velasco, Daniel; Sites, Robert W. (Zootaxa, 2016)
The Ambrysus hybridus Montandon species complex is revised and includes A. convexus Usinger, A. fuscus Usinger stat. rev., A. hybridus Montandon, A. lattini La Rivers, A. plautus Polhemus & Polhemus, A. spiculus Polhemus & Polhemus, A. thermarum La Rivers, and A. ultimus La Rivers. Ambrysus lariversi n. sp. is the ninth species in this complex and is described from Mexico. A. tridentatus La Rivers and A. woodburyi Usinger are proposed as junior synonyms of A. hybridus Montandon and for which a lectotype is designated. Most of the species in this complex occur only in Mexico, although A. thermarum is known only from the United States and A. hybridus occurs from the southwestern United States to southern Mexico and has the widest distribution of any species in this complex. Features uniting these species are related to male genitalia and structures associated with the male and female genitalia.